2021
DOI: 10.1093/jme/tjab057
|View full text |Cite
|
Sign up to set email alerts
|

Furuncular Myiasis by Dermatobia hominis (Diptera: Oestridae) in Wild Jaguars in the Amazon Rainforest

Abstract: Two individuals of the jaguar, Panthera onca (L.), were captured near the municipality of Presidente Figueiredo, Brazilian Amazon, during the years of 2017 and 2018. The jaguars presented furuncular myiasis caused by the human botfly Dermatobia hominis (L.) on the rear thighs and tail. This is the first record of infestation of D. hominis in P. onca in the Amazon region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…The literature consulted contains reports of furuncular myiasis in several species such as cattle ( Fernandes et al, 2008 ; Oliveira-Sequeira et al, 1996 ), dogs ( Deak et al, 2020 ; Ribeiro et al, 2001 ), wild animals ( May-Junior et al, 2021 ; Soares et al, 2021 ; Verocai et al, 2009 ) and even in humans ( Freitas et al, 2018 ; Pinos et al, 2014 ). The present study shows dermatobiosis in a domestic cat, only reported before in Brazil and Venezuela ( Campos et al, 2021 ; Marcial et al, 2003 ; Verocai et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…The literature consulted contains reports of furuncular myiasis in several species such as cattle ( Fernandes et al, 2008 ; Oliveira-Sequeira et al, 1996 ), dogs ( Deak et al, 2020 ; Ribeiro et al, 2001 ), wild animals ( May-Junior et al, 2021 ; Soares et al, 2021 ; Verocai et al, 2009 ) and even in humans ( Freitas et al, 2018 ; Pinos et al, 2014 ). The present study shows dermatobiosis in a domestic cat, only reported before in Brazil and Venezuela ( Campos et al, 2021 ; Marcial et al, 2003 ; Verocai et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%